146k views
5 votes
G(x) = 2x^2 + 3x – 9 if g(-3)

User Azulflame
by
4.6k points

2 Answers

3 votes

We are looking for G(-3) not g(-3). See the difference?

Replace every x you see with -3.

G(-3) = 2(-3)^2 + 3(-3) - 9

G(-3) = 2(9) - 9 - 9

G(-3) = 18 - 18

G(-3) = 0

Got it?

User Kiritushka
by
4.7k points
3 votes

Answer:

g(-3) = 0

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

g(x) = 2x² + 3x - 9

g(-3) is x = -3

Step 2: Evaluate

  1. Substitute: g(-3) = 2(-3)² + 3(-3) - 9
  2. Exponents: g(-3) = 2(9) + 3(-3) - 9
  3. Multiply: g(-3) = 18 - 9 - 9
  4. Subtract: g(-3) = 9 - 9
  5. Subtract: g(-3) = 0
User Perimosocordiae
by
5.5k points